Need for tracheostomy after lung transplant predicts decreased mid‐ and long‐term survival. Issue 1 (31st December 2019) - Huddleston, Stephen J.; Brown, Roland; Rudser, Kyle; Goswami, Umesh; Tomic, Rade; Lemke, Nicholas T.; Shaffer, Andrew W.; Soule, Matthew; Hertz, Marshall; Shumway, Sara; Kelly, Rose; Loor, Gabriel
Abstract: Background: Tracheostomy is an important adjunct for lung transplant patients requiring prolonged ventilation. We explored the effects of post‐transplant tracheostomy on survival and bronchiolitis obliterans syndrome after lung transplant. Methods: A retrospective, single center analysis was performed on all lung transplant recipients during the Lung Allocation Score (LAS) era. Risk factors for post‐transplant tracheostomy or death within 30 days were assessed. Kaplan‐Meier estimates and Cox proportional hazards models were used to examine the association between tracheostomy within 30 days after transplant and survival at 1 and 3 years. A total of 403 patients underwent single or bilateral lung transplant between May 2005 and February 2016 with complete data for 352 cases, and 35 patients (9.9%) underwent tracheostomy or died (N = 10, 2.8%) within 30 days. Results: In adjusted analyses, primary graft dysfunction grade 3 (PGD3) was associated with a composite end point of tracheostomy or death within 30 days (HR 3.11 (1.69, 5.71), P ‐value < .001). Tracheostomy within 30 days was associated with decreased survival at 1(HR 4.25 [1.75, 10.35] P ‐value = .001) and 3 years (HR 2.74 [1.30, 5.76], P ‐value = .008), as well as decreased bronchiolitis obliterans (BOS)‐free survival at 1 (HR 1.87 [1.02, 3.41] P ‐value = .042) and 3 years (HR 2.15 [1.33, 3.5], P ‐value = .002). Conclusion: Post‐transplant tracheostomy is a marker for advanced lung allograft dysfunction with significant reduction in long‐term overall and BOS‐free survival.